Integrated Nursing Intervention Theory in Providing Comfortableness to Increase Patient Well Being: Simple Theory Construction - Priyanto Priyanto; Achmad Fauzi Kamal; Debie Dahlia; Saptawati Bardosono (GLOBAL HEALTH SCIENCE GROUP, 2021)
This article shows that an integrated and compatible independent nursing intervention model approach is important to be able to hope of providing a strong theoretical basis for nurses on improving the wellbeing of acute coronary syndrome patients through a conceptual model of integrated nursing interventions during treatment in the hospital. The purpose of this article is to present a simple theoretical construction using a 7-step approach which includes: origin, meaning, logical adequacy, usefulness, generaliability and parsimony as well as testability, about integrative nursing intervention theory in providing comfort to improve patient well being. This type of research is a development research model with a simple theory construction model approach. The problems faced by patients with acute coronary syndrome most often are chest pain, anxiety and hemodynamics which can interfere the patient's well-being. Chest pain that is occurred due to coronary blockage has an impact on the fear of death and can affect hemodynamic stability. Anxiety is the most prominent stress and greatly disturbs the patient's psychological condition. The integrative nursing intervention model becomes a model approach that can be applied by nurses in nursing care services for patients with acute coronary syndrome. Therefore, the role of nurses as service providers should be able to make the best contribution through the application of an integrative nursing intervention model. This intervention model approach is expected to be able to improve patient well being during hospitalization.